INTEGRASI MATERI KEBENCANAAN PADA JENJANG SEKOLAH DASAR DI KECAMATAN NGARGOYOSO, JAWA TENGAH - Inge Ammelia; Diyah Sri Lestari; Ghulam Tsabat Al Ghazy; Yunus Aris Wibowo (Disaster Research Center, Universitas Sebelas Maret, Surakarta, Indonesia, 2022)
Karanganyar is an area that is prone to landslides, one of which is in Berjo Village, Ngargoyoso District. Educational integration is an effort to unify the process of changing one's attitudes and behavior in the eyes of the group in an effort to mature humans through learning. This study aims to determine the integration of disaster materials and educators' perceptions of each elementary school in landslide-prone areas, Ngargoyoso District. The approach used in this study is a quantitative approach using primary data through questionnaires and interviews. The sample technique used in this study used a purposive sampling technique with a research sample of 20 people divided into 16 teachers and 4 principals or 4 teachers and 1 principal at SD N 1 Kemuning, SD N 4 Kemuning, SD N 5 Kemuning, and SD IT Al-Hikmah. In this study, the importance of a teacher's perception of understanding disaster material to support efforts to reduce disaster risk and make fixed procedures for disaster preparedness in schools. The existence of educational knowledge in schools is expected to be an effective measure for the distribution of information regarding the integration of disaster materials. Keywords: Disaster, Materials, Integration